Pengaruh Kualitas Pelayanan, Kualitas Produk, Persepsi Harga, dan Word of Mouth terhadap Keputusan Pembelian - Nandha Sonaka; Heru Sutapa; Rafikhein Novia Ayuanti (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study aims to analyze the influence of service quality, product quality, price perception, and Word of Mouth on eyeglass purchasing decisions at Optik Anugerah Nganjuk. The background of this study is based on the increasing business competition in the optical sector and the increasing consumer awareness of the value, price, and quality of the products they consume. This study uses a quantitative approach with a survey method. The population in this study were all consumers of Optik Anugerah Nganjuk, with a sample of 88 respondents determined using a specific sampling technique. Data collection was carried out by distributing questionnaires compiled based on a Likert scale. The obtained data were analyzed using multiple linear regression methods to determine the influence of independent variables on the dependent variable. The results of the study indicate that partially service quality, price perception, and Word of Mouth have a significant effect on purchasing decisions, while product quality has no significant effect. However, simultaneously, all four independent variables have a significant effect on purchasing decisions. The findings of this study are expected to be strategic considerations for optical managers in improving service quality and the effectiveness of marketing strategies.